Answers

2015-09-30T15:31:40+05:30
LET (x-1) BE A FACTOR OF 4x^3-6x^2+9x-7
∴4(1)^3-6(1)^2+9(1)-7=0
⇒4-6+9-7=0
⇒13-13=0
∵0=0
∴(x-1) IS A FACTOR OF THE GIVEN POLYNOMIAL.
               i hope that this will help u.
0
2015-09-30T17:05:06+05:30
                 4x^2-2x+7

x-1 divided 4x^3-6x^2+9x-7
               4x^3-4x^2
               -        +
             _______________
                     -2x^2+9x
                     -2x^2+2x
                       +      -
               _________________
                           7x-7 
                           7x-7
                           -  +
               ____________________
                             0

there its a factor of given equation
 equation
0